Pheochromocytomas and Paragangliomas: Clinical and Genetic Approaches - Costa, Marcia Helena Soares; Ortiga-Carvalho, Tania M.; Violante, Alice Dutra; Vaisman, Mario (Frontiers in Endocrinology, 2015)
Pheochromocytomas (PCCs) and paragangliomas (PGLs) are neuroendocrine tumors derived from the chromaffin tissue. Diagnosis of these tumors is extremely important as they are linked to the hypertension syndrome with great cardiovascular morbidity and mortality. A great majority of PCCs and PGLs are sporadic and benign tumors; however, the classic idea of 10% exception of these features is changing. The description of new genes linked to familial forms of PCC/PGLs, such as succinate dehydrogenase (SDH) complex subunits, KIF1Bβ, EGLN1, TMEM127, and MAX, added to the well-known PCC familial syndrome (MEN2, VHL, and neurofibromatosis type 1) presents new challenges for diagnosis. In this review, we discuss the diversity of clinical and genetic approaches to this syndrome as well the diverse criteria that should guide genetic investigation.